Child Character Formation Through Islamic Religious Education - Mochamad Agus Cholil (STIKes Ibnu Sina Ajibarang, 2025)
This research is driven by curiosity and public concerns about the diverse characters of children or individuals in Indonesia. Society holds high expectations for children to receive proper character education so that they develop into individuals with strong character, noble morals, and the ability to live in accordance with Islamic law. Given this situation, it is necessary to conduct a study by examining various examples from the community who are currently or have previously engaged in the process of educating their children. The researcher conducted surveys and interviews with local people, obtaining a wide range of diverse responses. To achieve these objectives, this study employs qualitative-descriptive research methods with literature review techniques. The results indicate that early character education is crucial, and selecting appropriate methods aligned with Islamic teachings helps children develop faith, knowledge, practice, broad insight, good citizenship, and noble character that benefit all of humanity.